MOLECULAR DIAGNOSIS OF NEMATODE WORMS PARABRONEMA SKRJABINI IN CAMELS (Camelus dromedaries) IN IRAQ - Fadhil, Ali I.; Howaida H. Abed; Fadel, S. R.; Al-Zubaidi, M.Th. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The current study was designed for analysis of the pattern of the nucleotide sequence of the tissue DNA isolates based on the ITS2,28SrDNA gene by the traditional polymerase chain reaction. All amplicons were well suited for the prepared primer with size 873 bp . and identical ratio ranged 87.2- 98% of the same species, as included a high similarity of the isolates taken camels in Iran and Iraq related to Parabronema skrjabini . Phylogenic tree inferred the degree of relatedness between 28SrDNA sequences deposited in the international nucleotide bank sequence database (NCBI). The sequence of Parabronema skrjabini was recorded in the Genbank under accession number MT742154.1.